Análise do cumprimento das Normas Regulamentadoras aplicadas à utilização dos equipamentos de proteção individual e coletivo em canteiros de obras na cidade de Belém. - ALMEIDA, Newton José Guimarães (2024)
In recent years, the Civil Construction industry in Brazil has stood out as a major source of employment and income, however, along with economic expansion, the sector is currently ranked as the fourth segment of the economy that generates the most accidents at work. The city of Belém, despite its regional peculiarities, reflects national indices in a strong way. Accidents do not happen without cause, Brazilian labor legislation has a regulatory framework that aims to eliminate or minimize these causes, but these rules are often neglected and can lead to work accidents. This research has the general objective of analyzing compliance with the regulatory standards applied to the use of safety equipment on construction sites in the city of Belém-PA. For this purpose, the descriptive and exploratory research method was used, based on collected data in a restricted sample space to six regular construction sites in the city, in which observations of the working environment conditions were made in legislation applied compliance. In addition, social, cultural and professional data were collected from local workers through a proposed questionnaire, the answers to which were compiled generating graphs that, after being analyzed and compared to the theoretical framework, made it possible to conclude that a high percentage of workers have little or no training related to occupational safety which, combined with low levels of education and high labor turnover, contributes to low awareness regarding the effectiveness of safety equipment in mitigating workplace accidents.